Field study on the performance of a thermosyphon and mechanical refrigeration hybrid cooling system in a 5G telecommunication base station. (1st August 2022) - Meng, Fanxi; Zhang, Quan; Lin, Yaolin; Zou, Sikai; Fu, Jiyao; Liu, Baochang; Wang, Wei; Ma, Xiaowei; Du, Sheng
Abstract: The increases in power density and energy consumption of 5G telecommunication base stations make operation reliability and energy-efficiency more important. In this paper, a novel type of rack-level hybrid cooling system which combines a thermosyphon loop with a mechanical refrigeration loop was developed and applied in two parallel cabinets installed different operating powers of the communication equipment. Its performance was tested on-site in a real 5G telecommunication base station in transitional season at Wuhan city, China. Thermal safety and energy consumption under the normal and urgent operation modes were evaluated. The results showed that under the normal daily operation mode 1, communication equipment can be cooled effectively, but the power usage effectiveness value reached 1.59. Under the urgent mode 7, communication equipment can maintain safe operation for over 20 min. In view of this, five novel energy-saving operation modes 2–6 were proposed and tested. The cooling effect and energy consumption under different modes were analyzed and compared. Under the thermosyphon mode 6, the cooling system can only meet the cooling demand for one side of the cabinet when the outdoor temperature is around 20 °C. Compared to mode 1, mode 5 was recommended due to the 7–9 °C lower operating temperature and 27.3% decrease of energy consumption. Highlights: A novel hybrid cooling system was developed. The operating thermal performance and energy consumption of the system applied in a real 5G TBS were investigated. The performance of the cooling system was compared and analyzed.